Preclinical models for the study of Barrett's carcinogenesis. Issue 1 (5th July 2018) - Read, Matthew D.; Krishnadath, Kausilia K.; Clemons, Nicholas J.; Phillips, Wayne A.
Abstract: Barrett's esophagus (BE) is clinically significant, as it is the only known precursor lesion for esophageal adenocarcinoma. To develop improved therapies for the treatment of BE, a greater understanding of the disease process at the molecular genetic level is needed. However, achieving a greater understanding will require improved preclinical models so that the disease process can be more closely studied and novel therapies can be tested. Our concise review highlights progress in the development of preclinical models for the study of BE and identifies the most suitable model in which to test novel therapies.